STRESS AND PRESSURE IN STUDENTS BEFORE EXAMS - Trigulova T. A; Yunusova F. B (TADQIQOTLAR, 2026)
Abstract Stress is an unavoidable aspect of human life that significantly impacts students, particularly before exams. Academic pressure, coupled with high expectations from parents, teachers, peers, and self-imposed standards, can lead to anxiety, sleeplessness, and emotional strain. This study explores the multifaceted nature of pre-exam stress, examining its causes,  manifestations, and consequences on students’ physical, mental, and  social  well-being.    Factors  such  as  workload,  time  management,  health,  and emotional  resilience  are  considered,  alongside  the  effects  on  concentration,  sleep patterns, and interpersonal relationships. Understanding these stressors is crucial for developing effective coping strategies and support mechanisms. The study highlights the  importance  of  interventions  from  academic  institutions,  families,  and  students themselves to reduce stress, enhance mental health, and improve academic outcomes.